A dyadic typology of social desires in couples. Issue 4 (26th September 2017) - Czikmantori, Thomas; Hagemeyer, Birk; Engeser, Stefan
Abstract: Objective: Employing a couple‐centered approach to social motivation in intimate relationships, we developed a dyadic typology based on the ABC model of communal and agentic social desires. Method: Using latent profile analysis, 631 heterosexual couples (age women: M = 39.7, SD = 13.6; age men: M = 42.0, SD = 14.1) were categorized regarding both partners' self‐reported desires for closeness with partner, for affiliation with friends, and for being alone. Couple types were described using self‐reported indicators of relationship functioning. Relationship stability was assessed after 1 year, and in stable couples, social desires were reassessed to examine continuity and change. Results: We identified four motivational couple types. Three profiles showed similar orientations between partners and were labeled the communion, closeness, and distance couple types. Additionally, the distanced‐man type was characterized by a low desire for closeness and a high desire for being alone in men, but not women. The communion and closeness types showed better relationship functioning than the other types, and the distanced‐man type showed an increased rate of relationship break‐up. Conclusions: A couple‐centered, typological approach provides a viable way of studying complex dyadic motivational constellations and their consequences. This is beneficial for researchers as well as practitioners.